PERAN DAKWAH DIGITAL DALAM PENGEMBANGAN KEMAMPUAN BERDAKWAH MAHASISWA PRODI MANAJEMEN DAKWAH IAI AL-AZIS - Sahrul Rijal Muttaqin; Sobirin; Meity Suryandari (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This article examines the role of digital da'wah in developing students' da'wah skills. The first main problem of this study is how digital da'wah can contribute to the development of students' da'wah skills, which can be seen from the aspects of religious knowledge, communication skills, and mastery of digital media. The second main problem is the role of the da'wah management study program as a facilitator in supporting this process. The purpose of this study is to determine and understand how digital da'wah and the da'wah management study program play a role and facilitate the development of students' da'wah skills, including aspects of da'wah material mastery, communication skills, and the ability to manage media creatively and effectively. This research method uses a descriptive qualitative approach with student interviews. The study included six informants from the 2022, 2023, and 2024 classes of the Da'wah Management study program, as well as four lecturers teaching courses related to digital da'wah, as well as the head of the Da'wah Management study program. The results of the study indicate that digital da'wah significantly contributes to improving student competency in three main aspects: (1) Islamic knowledge, through easy access to da'wah materials from various trusted sources; (2) communication skills, particularly in crafting engaging, persuasive, and contextual da'wah narratives; and (3) mastery of digital technology, including visual content production, social media management, and virtual interaction with mad'u (students). The Da'wah Management study program supports this process through a practice-based curriculum, adaptive learning, digital content assignments, and the involvement of lecturers as direct mentors. Although challenges remain, including limited digital infrastructure and access to laboratory facilities, the established academic ecosystem is capable of fostering a generation of professional, adaptive, and contributing digital da'i. Keywords: Digital Da’wah, Preaching Skills, Diffusion of Innovation, Da’wah Management;